Üretim Kayıp Maliyetlerinin Belirlenmesi Ve Bir Uygulama - Tekin, İzlem (Fen Bilimleri Enstitüsü, 2009)
Bu çalışmada üretim birim performanslarının ölçülmesinde ingilizcede OEE (Overall Equipment Effectiveness) olarak ifade edilen “Toplam Tezgah Kullanım Etkinliği” yöntemi kullanılmıştır. OEE kullanılabilirlik, performans oranı ve kalite oranı değişkenlerinin bir fonksiyonu olarak ölçülmektedir. Uygulamanın yapıldığı işletmede öncelikle ingilizcede TPM (Total Productive Maintenance) olarak ifade edilen “Toplam Verimli Bakım” felsefesinde ki 16 büyük kayıp analiz edilmiş ve üretimde gerçekleşen kayıplar ile meydana gelme yerleri belirlenmiştir. OEE ile üretim performansı ölçülmüştür. Daha sonra maliyet hesaplamalarında daha kesin sonuçlar verdiği için Faaliyet Tabanlı Maliyetlendirme yöntemi felsefesindan faydalanılarak üretim birim maliyetleri, öncelikle faaliyetler daha sonra faaliyet maliyetleri hesaplanarak belirlenmiştir. Kayıplar ile maliyet faktörleri arasında ilişki kurularak, kayıp maliyetleri hesaplama yöntemi formülüze edilmiştir. Tüm kayıp maliyetleri hesaplandıktan sonra, iyileştirme çalışmalarında kullanılmak üzere önceliklendirme yapılarak kaynakların, kayıpların azaltılması için ayrılması sağlanmıştır.

In this study OEE ( Overall Equipment Effectiveness) metric is used for describing the individual manufacturing units performance. OEE is formulates as the fuction of availability efficiency, performance efficiency and quality efficiency and used in this study to identify the production losses of the manufacturing unit. First, the production losses must be identified, various losses in the production systems, their locations and occurance durations were determined using the TPM 16 big losses categories. Production losses rate and equipment performance rate were measured by using OEE. Second, The manufacturing cost and also production unit cost were computed by using ABC (Activity Based Costing) because ABC systems provides accurate computation. ABC methodology includes these steps; identifiying activities, determining activity cost drivers , computing the activity costs and finally, identifiying the production units or product costs. All sources’s costs in the production unit were computed. Third, losses converted into manufacturing cost. Losses and cost factors relationships were determined and their equations were given in the study. After estimated the total costs of each loss, we can obtain priority for manufacturing losses and their recoverable costs and organize the improvement activities like kaizen methods in TPM. The priority of improvement programs can be adjusted according to results of this analysis methods.
Determination Of Costs Resulting From Manufacturing Losses And An Application
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2009
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2009
Keywords: Faaliyet tabanlı maliyetlendirme; Toplam tezgah kullanım etkinliği; Kayıp maliyet; Activity based costing; Cost loss; OEE.